The free nutritious meal program in improving dietary habits and its impact on oral health - Nurfitri Amaliah; Maria Laurentia Sanjaya (Indonesian Journal of Dental Medicine, 2026)
Background: Oral health is a globally neglected issue, with dental caries affecting billions. The Indonesian government’s Free Nutritious Meal Program or Makanan Bergizi Gratis (MBG) aims to reduce malnutrition, but its specific impact on oral health requires evaluation. Purpose: to examine the MBG program in improving dietary habits and its subsequent impact on dental caries and oral health behavior. Methods: A comparative cross-sectional study was conducted at elementary school or Sekolah Dasar Negeri (SDN) Klampis Ngasem 3 and SDN Keputran 1 in Surabaya. Data on Caries Experience (deft/DMFT), Dietary Habits, Dental Health Behavior, and body mass index (BMI) were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: In the control group, dietary habits were a near-total predictor of caries (path coefficient 0.904, P=0.000), whereas this influence dropped to 0.541 in the intervention group. The program “decoupled” BMI from caries; BMI was a significant predictor in the control group (P=0.006) but became non significant in the intervention group (P=0.107). The model explained 83.5% of caries variance in the control group, compared to only 29.7% in the intervention group, suggesting the program mitigates primary dietary risks. Conclusion: MBG program effectively achieves the study’s aim by acting as a structural regulator that standardizes dietary intake and improves oral health outcomes. By providing a balanced nutritional baseline, the program “decouples” the link between BMI and tooth decay, neutralizing physical status as a risk predictor. While the program provides a protective foundation, individual dental health behaviors remain essential for complete prevention.